Next generation human brain models: engineered flat brain organoids featuring gyrification. (15th March 2021) - Rothenbücher, Theresa S P; Gürbüz, Hakan; Pereira, Marta P; Heiskanen, Arto; Emneus, Jenny; Martinez-Serrano, Alberto
Abstract: Brain organoids are considered to be a highly promising in vitro model for the study of the human brain and, despite their various shortcomings, have already been used widely in neurobiological studies. Especially for drug screening applications, a highly reproducible protocol with simple tissue culture steps and consistent output, is required. Here we present an engineering approach that addresses several existing shortcomings of brain organoids. By culturing brain organoids with a polycaprolactone scaffold, we were able to modify their shape into a flat morphology. Engineered flat brain organoids (efBOs) possess advantageous diffusion conditions and thus their tissue is better supplied with oxygen and nutrients, preventing the formation of a necrotic tissue core. Moreover, the efBO protocol is highly simplified and allows to customize the organoid size directly from the start. By seeding cells onto 12 by 12 mm scaffolds, the brain organoid size can be significantly increased. In addition, we were able to observe folding reminiscent of gyrification around day 20, which was self-generated by the tissue. To our knowledge, this is the first study that reports intrinsically caused gyrification of neuronal tissue in vitro. We consider our efBO protocol as a next step towards the generation of a stable and reliable human brain model for drug screening applications and spatial patterning experiments.